Amityville turkey day [videorecording (DVD)] - Collazo, Will, Jr; Prescott, Julie Anne; Kiseleski, Steven; Perry, David; Flowers, Amanda (SRS Cinema LLC, 2024)
"A turkey from hell comes home for dinner on Thanksgiving, terrorizing the film set of an indie horror film. It's trukey time mother clucker!"--